2017
DOI: 10.1038/ncomms14802
|View full text |Cite
|
Sign up to set email alerts
|

A CD47-associated super-enhancer links pro-inflammatory signalling to CD47 upregulation in breast cancer

Abstract: CD47 is a cell surface molecule that inhibits phagocytosis of cells that express it by binding to its receptor, SIRPα, on macrophages and other immune cells. CD47 is expressed at different levels by neoplastic and normal cells. Here, to reveal mechanisms by which different neoplastic cells generate this dominant ‘don't eat me' signal, we analyse the CD47 regulatory genomic landscape. We identify two distinct super-enhancers (SEs) associated with CD47 in certain cancer cell types. We show that a set of active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
172
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 57 publications
10
172
0
Order By: Relevance
“…Previous studies including breast cancer identified that the promoter region for the CD47 gene is regulated by binding of several transcription factors, including MYC and NF-κB (8,9). However, the exact mechanism behind the overexpression of CD47 in cancer cells is insufficiently understood (10).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies including breast cancer identified that the promoter region for the CD47 gene is regulated by binding of several transcription factors, including MYC and NF-κB (8,9). However, the exact mechanism behind the overexpression of CD47 in cancer cells is insufficiently understood (10).…”
mentioning
confidence: 99%
“…In a recent study published in Nature Communications by Betancur et al, a CD47-associated specific regulatory genomic locus, a so-called "super-enhancer" (SE), was identified (10). In general, a SE constitutes a gene region with strong enrichment of transcriptional co-activators as mediator (MED1) (11).…”
mentioning
confidence: 99%
See 3 more Smart Citations